Learning styles identification and analysis to improve teaching in an engineering subject (Research, Society and Development, 2020)
Teaching in engineering courses can be improved by the knowledge of learning styles. Teaching practices understand are important to incorporate them efficiently in the classroom, looking for their strengths and distributing the similarities and differences between them. The proposed work investigated the predominant learning styles of students in a subject in the Sanitary and Environmental Engineering course using the Felder-Silverman method and applied teaching techniques to reach all students styles. The results indicate preferentially active, sensory, visual and sequential students, but with several variations, it is important to conduct modifications and improvements in the teaching method to achieve the maximum of all the styles observed. The subject was added practical classes in the field and computer lab, technical visits, activity reports and many motivational practices. In addition, modifications were made to the course evaluation process, which provided a higher level of learning, reflecting the increase in the number of approved students in relation to the previous semesters, reaching 90% of class approval.